2020
DOI: 10.7150/thno.45994
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer detection via Galectin-1-targeted Thermoacoustic Imaging: validation in an in vivo heterozygosity model

Abstract: Purpose: To investigate the feasibility of microwave-induced thermoacoustic imaging (MTAI) in detecting small pancreatic tumors (< 10 mm in diameter) and to complement the limitation of current clinical imaging methods. Methods: A home-made MTAI system composed of a portable antenna and pulsed microwave generator was developed. The thermoacoustic nanoparticles were composed of the galectin-1 antibody for targeting pancreatic tumors and Fe 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…GAL-1 has been found in multiple tumor cells, including melanoma, lung cancer [30], pancreatic cancer [31], bladder cancer [32], thyroid cancer [33], cervical cancer [34], and colorectal cancer [35]. In the present study, we showed that the GAL-1 protein and LGALS1 mRNA levels in GC tissue were signi cantly higher than those in NGCT, suggesting that GAL-1/LGALS1 is associated with the malignant biological behavior of GC.…”
Section: Discussionsupporting
confidence: 53%
“…GAL-1 has been found in multiple tumor cells, including melanoma, lung cancer [30], pancreatic cancer [31], bladder cancer [32], thyroid cancer [33], cervical cancer [34], and colorectal cancer [35]. In the present study, we showed that the GAL-1 protein and LGALS1 mRNA levels in GC tissue were signi cantly higher than those in NGCT, suggesting that GAL-1/LGALS1 is associated with the malignant biological behavior of GC.…”
Section: Discussionsupporting
confidence: 53%
“…GAL-1 has been found in multiple tumor cells, including melanoma, lung cancer [ 31 ], pancreatic cancer [ 32 ], bladder cancer [ 33 ], thyroid cancer [ 34 ], cervical cancer [ 35 ], and colorectal cancer [ 36 ]. The results of the present study demonstrated that the GAL-1 protein and LGALS1 mRNA levels in GC tissue were significantly higher than those in NGCT, suggesting that GAL-1/ LGALS1 is associated with the malignant biological behavior of GC.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Qin et al explored Fe 3 O 4 nanoparticles modied with galectin-1 antibody in the targeted microwave-induced thermoacoustic imaging of pancreatic cancer, demonstrating an enhanced contrast ratio. 44 Carbon nanotubes (CNT) are another nanomaterial that has attracted the interest of MW researchers. An early analysis of the nanomaterial in 2009 indicated that "When carbon nanotubes are exposed to microwaves, strong absorptions are observed, producing intense heating, outgassing, and light emission".…”
Section: Nanoparticles and Nanomaterials As Potential Contrast Agents For Microwave Imagingmentioning
confidence: 99%
“…In 2020, Qin et al explored Fe 3 O 4 nanoparticles modified with galectin-1 antibody in the targeted microwave-induced thermoacoustic imaging of pancreatic cancer, demonstrating an enhanced contrast ratio. 44 …”
Section: Nanoparticles and Nanomaterials As Potential Contrast Agents For Microwave Imagingmentioning
confidence: 99%